Cohabitation as a young adult: examining relationship interactions & outcomes and financial characteristics and economic well-being - Lawson, Derek Richard (Kansas State University, 2019)
This dissertation employed two different frameworks to investigate the effects that cohabitation and finances have on young adult couples’ relationships using the National Longitudinal Survey of Youth 1997 (NLSY97) and the Marriage Matters Panel Survey of Newlywed Couples, Louisiana. Understanding young adult’s financial and relationship characteristics and outcomes is increasingly important for the financial planning profession given the shift towards holistic financial planning. Cohabitation has been increasing each decade while research indicates it to have drastic financial and relational consequences. It is important to understand how cohabitation impacts young adults’ financial and relational lives. Essay one investigated whether financial implications and perceived benefits and costs in a relationship mediated the relationship between relationship quality at Time 1 (i.e., age 24) and relationship quality at Time 3 (i.e., age 26), and the subsequent impact of whether the relationship dissolves. Using a sample of 508 young adults, 330 of which had cohabited prior to marriage and 178 which had not, essay one revealed no major differences between those who cohabited and those who did not. Initial relationship quality did have positive effects on later relationship quality and staying in a relationship. Financial assets, debt, and income appeared to have no effect on relationship quality. Essay two examined the rate of change in relationship satisfaction in a group of 479 recently married couples. The results showed that cohabitation had no effect on initial levels of, and the rate of change in, relationship satisfaction experienced by both husbands and wives. Income and debt had no effect on the trajectories of relationship satisfaction, but perceived economic well-being did appear to have a positive association with the initial levels of relationship satisfaction experienced by both wives and husbands. Essay three employed an actor partner interdependence model (APIM) to examine how economic hardships such as low income, debt, and not having a job prior to marriage influence not only the respondent’s economic pressure (as measured through economic well-being) but also their partner’s economic pressure. Further, the study tested how economic pressure influences both the warmth and conflict experienced by themselves, as well as their partner, and ultimately how that all influences their own relationship satisfaction and the marital perceptions of their partner. Further, to tease out the effect of cohabitation, the current study employed a multiple group comparison on those who cohabited prior to marriage against those who did not. Consistent with essay one and two, cohabitation did not have much of an impact but results of essay three indicate that there are both actor and partner effects on our relationship outcomes when finances are concerned. Overall, results indicate that with data of this millennium, cohabitation may not have as detrimental effects to the financial and relational lives of young adults as previously thought. Financial and mental health professionals can utilize actor partner frameworks in their work with clients to ensure both couples are on track and working together.
Keywords: Cohabitation; Relationship satisfaction; Economic well-being